INOVASI KEPALA SEKOLAH UNTUK MENINGKATKAN KOMPETENSI PROFESIONAL GURU PENDIDIKAN AGAMA ISLAM - Zaka, Avesina Qodli; Mustofa, Triono Ali (Program Studi Pendidikan Agama Islam Fakultas Ilmu Tarbiyah Dan Keguruan, 2023)
Islamic religious education has a central role in shaping the character and moral values of students. To ensure quality Islamic religious education, Islamic religious education teachers need to have high professional competence. One of the key elements in improving the professional competence of these teachers is the important role that principals play in fostering innovation. The type of research used is Field Research with a phenomenological approach. Qualitative research with field research strategies is research on the realization of people's social life directly. To check the validity of the data obtained by researchers using triangulation. Triangulation is a multimethod approach that researchers take when collecting and analyzing data. This research explores how school principals can innovate in improving the professional competence of Islamic religious education teachers. Through a comprehensive literature review and case studies from several successful schools, the research identifies innovative strategies that principals can implement. The results showed that innovative principals tend to facilitate a variety of training and professional development for teachers, encourage collaboration among teachers to share experiences and resources, and design teacher performance appraisal programs that focus on improving competencies. This research emphasizes the importance of the role of school principals in creating an environment that supports innovation, which in turn contributes to the improvement of the professional competence of Islamic religious education teachers. These findings have important implications in ongoing efforts to improve the quality of Islamic religious education and shape a more qualified and moral generation.